Survey on Black Hole and Gray Hole Attacks in MANET - Nachammai, M; Radha, N (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad hoc Network (MANET) is one of the most promising technologies in the recent years. In MANET, a wireless network is quickly formed using mobile nodes. Because of its characteristics such as open and undefined medium, limited resources, offering a secure data transmission in presence of malicious nodes in the network is main issues of the MANET. The black hole and gray hole attacks are major security threats in MANET, in which the packets are dropped in intermediate nodes. The main objective of this paper is to study the techniques used to eliminate the packet drop in intermediate nodes using malicious node detection techniques. In this paper, various malicious node detection methods such as Local anomaly detection and Cooperative anomaly detection , Fuzzy and wavelet transform based IDS system , Modified DSR protocol , Kullback-Leibler divergence approach, FireCol , hash function based method and cooperative bait detection scheme (CBDS) are studied and analyzed. The findings of this work proved that the cooperative bait detection achieves better results than the other approaches in terms of packet delivery ratio and end-to-end delay.